Prescription Medication Obtainment Methods and Misuse. Issue 4 (July 2015) - Bouland, Daniel Tyler; Fine, Eric; Withers, David; Jarvis, Margaret
<x xml:space="preserve">Abstract</x> Background: Abuse of prescription medications is an ever-expanding epidemic in the United States. Objective: This study intends to help provide physicians with more knowledge about the behaviors that patients with a substance use disorder may exhibit in an effort to obtain medications. Design: Patients who were willing to participate in the survey were interviewed by a physician. Setting: Patients were screened, selected, and interviewed while participating in an inpatient rehabilitation program. Results: Thirty-six patients completed the survey. There was a mean of 50.2 prescriptions per person. An average of 1.2 states was utilized by the surveyed patient population. There was an average of 2.11 providers seen per patient. Data show that 78% of patients surveyed utilized more than one pharmacy. The type of medications obtained by respondents were as follows: opioids, 35 (97.2%); sedative-hypnotics, 17 (47.4%); and amphetamines, 2 (5.5%). Seventy-five percent of patients (27 of the 36) stated that they feigned symptoms in attempts to obtain prescriptions. Two patients used a falsified (via mislabeling) magnetic resonance image of injury. Two patients paid a physician outright for the prescription. Three patients (8.3%) stated they would physically harm themselves in an attempt to obtain prescription medications. Conclusions: It may be noted that patients seeking prescription medications tend to utilize more than one physician and more than one pharmacy. On the basis of survey results, it seems that primary care and pain management physicians are considered the easiest venues to obtain prescription medications. It suggests that patients will go to great lengths to obtain prescription medications.